Strategies of South African companies competing with multinationals in local markets - Nkwanyana, Astrid (University of the Witwatersrand, Johannesburg, 2023)
As emerging markets are becoming more enticing to multinationals, the highly competitive leisure footwear industry is also seeing new upcoming local companies in South Africa face competition from these established multinationals. In addition, customers are influenced by various aspects of the markets. Therefore, it is vital to investigate customers’ attitudes and perceptions towards the marketing strategies used by these local and global companies. Using a qualitative research design through one-on-one interviews, the study interviewed ten respondents that are sports shoe customers ranging from fitness enthusiasts and operational staff in the fitness industry to a hip hop fan. Respondents were required to be users of leisure footwear to have in-depth knowledge of their preferred brands. Secondary data was also collected from various company websites and online publications, as well as academic journals. The research results provide insights into the strategies used by local and global footwear brands in South Africa, such as product innovation, brand image, local awareness, network access and collaboration. Findings show that product innovation influences customers to buy sneakers as most believe comfort is important in their fitness journey. Customers’ attitude towards brand image is positive as they believe in the brand, which motivates them to buy the sneakers. Importantly, 70% of the customers are influenced to buy sneakers by icons they look up to, and most respondents can access the brands they want to buy. Whilst most respondents felt global companies were not locally aware, this did not influence their buying
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Product innovation; Brand image; Local awareness; Collaborations; Network access; Marketing strategies; Competition; Customer attitudes; SDG-8: Decent work and economic growth